IMPLEMENTASI PERAN DIVISI KEIMIGRASIAN DALAM PENYELIDIKAN TINDAK PIDANA KEIMIGRASIAN (Studi Pada Kantor Wilayah Kementerian Hukum dan HAM Sumatera Barat) - Fitriahsani Fitriahsani (UNES Journal of Swara Justisia, 2018)
Immigration investigations are carried out by the Immigration Officer as regulatedin Article 74 of Law Number 6 of 2011 concerning Immigration. The current globaldevelopments have pushed the mobility of the world population from one country toanother, which can have a positive and negative impact. In reality there are still manyimmigration violations committed by foreigners visiting the country of Indonesia. Based onthe results of the study concluded: First that the implementation of the role of theImmigration Division of the Regional Office of the Ministry of Justice and Human Rightsof West Sumatra in the investigation of immigration crimes is still less than optimal interms of prosecution and immigration control. Secondly, the obstacles encountered in theinvestigation of immigration crimes were due to the lack of quality and quantity of humanresources in immigration PPNS, inadequate allocation of funds and operational facilities,lack of community awareness about the presence and activities of foreigners around themand difficulties in collecting evidence and witnesses. Third, efforts to overcome obstaclesto investigating immigration crimes are carried out by improving the quality and quantityof immigration PPNS human resources by providing regular training, providing foreignlanguage courses, disseminating immigration laws, further improving coordinationbetween relevant agencies, especially the police and prosecutors, as well as increasingsupervision of foreigners who come out, enter and carry out activities in the territory ofIndonesia.